ANALISIS TEOLOGIS KELOMPOK YANG DIMETERAIKAN ITU: 144.000 BERDASARKAN KITAB WAHYU 7 DAN WAHYU 14 DI JEMAAT CIMINDI RAYA BANDUNG - Josephin Andriano Aruan; Gerry C. J. Takaria (Fakultas Filsafat Universitas Advent Indonesia, 2017)
In this research, writer did a research about the interpretation of “144.000 people”based on Revelation 7 and 14. This research includes 3 parts, those are: (1) Literallyor symbolically, which in this case there are two different comprehensions based ontwo theories about who the 144.000 is. Many experts stated that the 144.000 isphysical Israel and others stated that it is spiritual Israel. About the number, manyexperts said that it is the literal number and others said it is just a symbol; (2) Thesymbol of the characteristics of the 144.000; (3) The fulfillment of sealing of the144.000. Writer divided the research into two parts. They are theory research andfield research. The result of the theory research about the group of 144.000 foundout that 144.000 in Revelation 7 and 14 is perceived as symbolical. The group of144.000 is spiritual Israel proved by no tribe of Dan in the group and because it issymbolical, the number then perceived also to be symbolical. The Characteristics ofthis group are: They follow the Lamb wherever the Lamb goes illustrate that theyhave a loyalty to the truth of God and to God itself, they are virgin show that theyhave purity in character, the ones who don’t defile their faith; the group is notinvolved in the falsification and the spiritual adultery. This group stays faithful toGod and to the God’s truth. The fulfillment of the 144.000 before second coming ofChrist. The Result of the field research, through questionnaires distributed to 45members of Cimindi Raya Bandung Seventh-Day Adventist Church, contains 19points of statement and divided in three indicators founded the Statement of 6, 10, 12and 14 church members still undecided.